Blaise Pascal’s Mechanical Calculator: Geometric Modelling and Virtual Reconstruction - José Ignacio Rojas-Sola; Gloria del Río-Cidoncha; Arturo Fernández-de la Puente Sarriá; Verónica Galiano-Delgado (Machines, 2021)
This article shows the three-dimensional (3D) modelling and virtual reconstruction of the first mechanical calculating machine used for accounting purposes designed by Blaise Pascal in 1642. To obtain the 3D CAD (computer-aided design) model and the geometric documentation of said invention, CATIA V5 R20 software has been used. The starting materials for this research, mainly the plans of this arithmetic machine, are collected in the volumes Oeuvres de Blaise Pascal published in 1779. Sketches of said machine are found therein that lack scale, are not dimensioned and certain details are absent; that is, they were not drawn with precision in terms of their measurements and proportions, but they do provide qualitative information on the shape and mechanism of the machine. Thanks to the three-dimensional modelling carried out; it has been possible to explain in detail both its operation and the final assembly of the invention, made from the assemblies of its different subsets. In this way, the reader of the manuscript is brought closer to the perfect understanding of the workings of a machine that constituted a major milestone in the technological development of the time.